Effects of Excess Iron on the Retina: Insights From Clinical Cases and Animal Models of Iron Disorders - Shahandeh, Ali; Bui, Bang V.; Finkelstein, David I.; Nguyen, Christine T. O. (Frontiers in Neuroscience, 2022)
Iron plays an important role in a wide range of metabolic pathways that are important for neuronal health. Excessive levels of iron, however, can promote toxicity and cell death. An example of an iron overload disorder is hemochromatosis (HH) which is a genetic disorder of iron metabolism in which the body’s ability to regulate iron absorption is altered, resulting in iron buildup and injury in several organs. The retina was traditionally assumed to be protected from high levels of systemic iron overload by the blood-retina barrier. However, recent data shows that expression of genes that are associated with HH can disrupt retinal iron metabolism. Thus, the effects of iron overload on the retina have become an area of research interest, as excessively high levels of iron are implicated in several retinal disorders, most notably age–related macular degeneration. This review is an effort to highlight risk factors for excessive levels of systemic iron buildup in the retina and its potential impact on the eye health. Information is integrated across clinical and preclinical animal studies to provide insights into the effects of systemic iron loading on the retina.